Relevance of chronotype for eating patterns in adolescents - Roßbach, Sarah; Diederichs, Tanja; Nöthlings, Ute; Buyken, Anette E; Alexy, Ute (Chronobiology international, 2018)
During adolescence, a shift from morningness to eveningness occurs, yet school continues to start early in the morning. Hence, adolescents are at risk for social jetlag, i.e. a discrepancy between biological and social timing. It remains to be determined whether chronotype associates with daily and daytime-specific eating patterns during this potentially critical period. Therefore, the aim of the present study was to investigate whether chronotype is decisive for daily eating patterns [total energy intake (TEI, kcal), total macronutrient intake (% of TEI), eating occasion frequency (n/day), meal frequency (n/day), snack frequency (n/day), duration of nightly fasting], or daytime-specific eating patterns [morning (before 11 am) energy intake (% of TEI), morning macronutrient intake (% of morning energy intake), regular breakfast skipping (no morning energy intake at least on 2 of 3 days, yes/no), evening (after 6 pm) energy intake (% of TEI), evening macronutrient intake (% of evening energy intake), regular dinner skipping (no evening energy intake at least on 2 of 3 days, yes/no)] in German adolescents. Chronotype was assessed by use of the Munich Chronotype Questionnaire and is defined as the midpoint of sleep corrected for sleep-debt accumulated over the workweek (the later the midpoint of sleep, the later the chronotype). A total of 223 participants (10-18 years) provided 346 questionnaires and concurrent 3-day weighed dietary records. Associations between chronotype and eating patterns were analyzed cross-sectionally using multivariable linear and logistic mixed-effects regression models. Adolescents with earlier and later chronotypes did not differ in their daily eating patterns. With respect to daytime-specific eating patterns, 1 h delay in chronotype was associated with 4.0 (95% CI 2.5-6.6) greater odds of regular breakfast skipping (p < 0.0001). In addition, later chronotype was associated with higher evening energy intake (p = 0.0009). In conclusion, our data show that a later chronotype among adolescents is associated with a shift of food consumption toward later times of the day. Hence, adolescents' eating patterns appear to follow their internal clock rather than socially determined schedules.